Study of the Q′ (Q)-phase precipitation in Al–Mg–Si–Cu alloys by quantification of atomic-resolution transmission electron microscopy images and atom probe tomography - Ding, Lipeng; Orekhov, Andrey; Weng, Yaoyao; Jia, Zhihong; Idrissi, Hosni; Schryvers, Dominique; Muraishi, Shiji; Hao, Longlong; Liu, Qing (Journal of Materials Science, 2019)
The precipitation mechanism of the Q phase in Al–Mg–Si–Cu alloys has long been the subject of ambiguity and debate since its metastable phase (Q′) has the same crystal structure and similar lattice parameters as its equilibrium counterparts. In the present work, the evolution of the Q′ (Q) phase during aging is studied by combination of quantitative atomic-resolution scanning transmission electron microscopy and atom probe tomography. It was found that the transformation from the Q′ to the Q phase involves changes of the occupancy of Al atoms in atomic columns of the Q′ (Q) phase. The Al atoms incorporated in the Cu, Si and Mg columns are gradually released into the Al matrix, while mixing between Cu and Si atoms occurs in the Si columns. This transformation process is mainly attributed to the low lattice misfit of the equilibrium Q phase. Besides, the formation of various compositions of the Q phase is due to the different occupancy in the atomic columns of the Q phase. The occupancy changes in the columns of the Q phase are kinetically controlled and are strongly influenced by the alloy composition and aging temperature.